Libraries in the information age : an introduction and career exploration - Fourie, Denise K.; Dowell, David R. (Santa Barbara, Calif. : Libraries Unlimited, 2009)
The book begins by examining the redefined and revitalized role of libraries in the era of electronic information, then provides historical background on the evolution of libraries.
Includes bibliographical references and index.
osc 08/05/13; osa 26/09/14
Loans
Keywords: Library science; Library science - vocational guidance